(untitled) (SNPRC Journal, 2023)
Arthashastra written by Kautilya is a treatise written to train a future king. The treatise has been divided in 15 books. Its first book provides a detail description of education pedagogy and related topic. Chapters on Knowledge, curriculum and the requisite of the learned scholars give an outline of education system in Kautiliya times. At the same time Kautiliya Arthashastra declares that main object of his education and training is to develop mental power of his student. The mental power is control of senses. This article is an effort to analyze the Kutiliya view on education and teaching methodology. The methodology of this study is mainly descriptive and analytical. Modern tools have been used to analyze Kautiliyan education Pedagogy.